Counterintuitive Pseudoscience Propagates by Exploiting the Mind’s Communication Evaluation Mechanisms - Mermelstein, Spencer; German, Tamsin C. (Frontiers in Psychology, 2021)
Epidemiological models of culture posit that the prevalence of a belief depends in part on the fit between that belief and intuitions generated by the mind’s reliably developing architecture. Application of such models to pseudoscience suggests that one route via which these beliefs gain widespread appeal stems from their compatibility with these intuitions. For example, anti-vaccination beliefs are readily adopted because they cohere with intuitions about the threat of contagion. However, other varieties of popular pseudoscience such as astrology and parapsychology contain content that violates intuitions held about objects and people. Here, we propose a pathway by which “counterintuitive pseudoscience” may spread and receive endorsement. Drawing on recent empirical evidence, we suggest that counterintuitive pseudoscience triggers the mind’s communication evaluation mechanisms. These mechanisms are hypothesized to quarantine epistemically-suspect information including counterintuitive pseudoscientific concepts. As a consequence, these beliefs may not immediately update conflicting intuitions and may be largely restricted from influencing behavior. Nonetheless, counterintuitive pseudoscientific concepts, when in combination with intuitively appealing content, may differentially draw attention and memory. People may also be motivated to seek further information about these concepts, including by asking others, in an attempt to reconcile them with prior beliefs. This in turn promotes the re-transmission of these ideas. We discuss how, during this information-search, support for counterintuitive pseudoscience may come from deference to apparently authoritative sources, reasoned arguments, and the functional outcomes of these beliefs. Ultimately, these factors promote the cultural success of counterintuitive pseudoscience but explicit endorsement of these concepts may not entail tacit commitment.